Pengaruh Support Group Terhadap Psychological Well Being Penderita HIV/AIDS - Ima Lutfiana; Endang R. Surjaningrum (JIP (Jurnal Intervensi Psikologi), 2010)
The study aimed to explore the influence of a Support Group (SG) to the psychological well being of HIV/AIDS patients in Blitar. The study employed the ex-post-facto method using static group comparison approach. There were 20 people with HIV/AIDS participate in the study, consisted of 10 patients who joined SG for at least six months and those who did not join. The data was collected using the 42 items Psychological Well Being Scale. The independent sample t-test resulted that there was a significant difference between those two groups indicated by t - 2.250 (p < 0.05). it can be concluded from the result that participation of HIV/AIDS patients to a Support Group gave impact to their psychological well being. The process of Support Group in giving rise to the psychological well being was discussed.Â Keywords: Support Group, Psychological Well Being, HIV/AIDS